Pengaruh Kualitas Produk, Harga Dan Pelayanan Terhadap Keputusan Pembelian Konsumen Pada Produk Skincare - Divia Dea Ananda; Budi Wahono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of Product Quality, Price, and Service Quality on Consumer Purchasing Decisions on Skincare Product.The data used in this study uses primary data by distributing questionnaires to respondents. The study population is students of the Faculty of Economics and Business, Islamic University of Malang with a total sample of 94 students. The sampling technique used purposive sampling. Data collection techniques using questionnaires and data analysis tools. The results of this study indicate that partially Product Quality, Price, and Service Quality has a significant positive efect on Consumer Purchasing Decisions on Skincare Product. While simultaneously has an effect between Product Quality, Price, and Service Quality variables on Consumer Purchasing Decisions on skincare Product..Keywords: Product Quality, Price, Service Quality and Purchasing Decisions